Meniere's Disease - Bahmad, Fayez Jr (IntechOpen, 2020)
Dizziness and vertigo are symptoms related to peripheral vestibular disorders. These are among the most common complaints in medical offices, and knowledge of the major diseases affecting this system is of fundamental importance to the specialist in otolaryngology. In recent years, great advances have been made in otoneurology, which, coupled with increasing knowledge in the field of neurosciences, have substantially modified the approach of the patient with balance complaints. This book studies the most polemic of these vestibular diseases, Ménière's disease.